A project manager's book of tools and techniques : a companion to the PMBOK Guide - Dionisio, Cynthia Snyder, 1962- (Wiley, 2018)
"This valuable companion to the Project Management Institute'sA Guide to the Project Management Body of Knowledge (PMBOK Guide) ; Sixth Edition presents comprehensive examples and explanations of the tools and techniques presented in thePMBOK Guide. Designed specifically to assist both new and experienced project managers in handling all aspects of a project, this title explins the how ; when it comes to project management theory. Concrete examples of tools for project managers will fill the gap in this PM knowledge area and provide necessary guidance for both practicing project managers and students"--